Exercise prescription in the management of rheumatoid arthritis - K. Nolte; D.C. Janse van Rensburg (South African Family Practice)
Background: Over the last few years, the types of exercises prescribed for patients with rheumatoid arthritis (RA) have changed. There is also increasing knowledge on the physical status and physical activity levels of these patients. This article aims to give an overview of the physical status, physical activity levels and appropriate exercise prescription for patients with RA.